Analisis Netnografi Lirik Lagu Dua Ade-Kaka sebagai Jembatan Merawat Imajinasi dan Relasi Antaragama - Jovico Onis Samallo; Jourlief J Samallo (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article aims to analyze the relationship between the Nusalaut community and the Ambalau community in using songs as a bridge to maintain memories and inter-religious relations. Focus on folklore that is sung and developed in the Nusalaut community and the Ambalau community, which then becomes a collective memory, strengthening relations between the lives of two groups of people with different religions. Dua adi-kaka's song becomes a supporting medium in interpreting the stories of previous generations in the reality of gandong adi-kaka as inter-religious spirituality in the theological process. The collective imagination of the Nusalaut people and the Ambalau people in songs is analysed using a socio-anthropological approach. Using qualitative research and netnographic methods, as well as efforts to obtain data on the meaning of songs through virtual participant observation, interviews, and literature, In the end, the research produced the finding that song imagination in the lives of the Nusalaut and Ambalau people can strengthen gandong relationships as well as transform destructive imaginations that threaten community unity.